Aphid wing polyphenism and conspecific egg cannibalism affect the developmental and reproductive performance of Chrysoperla carnea - Rashed, Ahmed A.; Ramadan, Marwa M.; Shalaby, Mona M.; El-Harairy, Amged; Bayoumy, Mohamed H. (Frontiers in Insect Science, 2025)
Aphid polyphenism and egg cannibalism may have nutritional consequences for the development, survival, and reproduction of predatory insects. Although predators have the same probability of attacking winged and wingless morphs in natural conditions, an increment in the proportion of winged morphs dispersed under predation risk may have a negative effect on predator feeding by reducing the size of the wingless form available on the plant. However, the wingless aphids may be richer in nutritional value than the dispersed winged aphids. Therefore, the nutritional consequences of aphid morphs and egg cannibalism for development, survival, 10-clutch fecundity and fertility, and the time needed for 10 clutches of eggs Chrysoperla carnea were addressed via a series of experiments. Wingless aphids accelerated the total development and increased the survival of C. carnea compared to the winged aphids. Furthermore, feeding with the wingless form increased the 10-clutch fecundities and fertilities, and reduced the days needed for 10 clutches of eggs. Neonate larvae of C. carnea that devoured two conspecific eggs took a shorter time with an acceleration in the overall development of C. carnea. Immature mortality was higher in controls than in the cannibalism treatment. Reproductive benefits were obvious in females permitted to consume two conspecific eggs during their first instar compared to those that did not. However, the time needed for 10 ovipositions did not differ between both groups. These findings are ecologically significant because C. carnea females are able to adapt to the stresses imposed by nature without needing winged aphid prey to distribute their eggs widely, as their larvae can grow on their own eggs and gain developmental and reproductive benefits from such behavior when prey availability or quality is low.